2020
DOI: 10.1093/cid/ciaa1053
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level Association of Influenza Infection With Subsequent Pneumonia: A Case-control and Prospective Cohort Study

Abstract: Background Pneumonia is a leading cause of mortality worldwide. Influenza may result in primary pneumonia or be associated with secondary bacterial pneumonia. While the association with secondary pneumonia has been established ecologically, individual-level evidence remains sparse and the risk period for pneumonia following influenza poorly defined. Methods We conducted a matched case-control study and a prospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Indeed, almost all children aged 12–23 months had MAARIs, and more than one in five tested positive for RSV and one in 10 for influenza. The incidence of respiratory viruses among this young age group is important because younger children are also at highest risk of viral 14 and bacterial pneumonias 15 and subsequent hospitalizations 16 . Such a burden suggests the value of continued investment in Ecuador's pharmaceutical and nonpharmaceutical interventions to prevent respiratory illnesses, which were associated with an annual productivity loss of US$152 million 17 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, almost all children aged 12–23 months had MAARIs, and more than one in five tested positive for RSV and one in 10 for influenza. The incidence of respiratory viruses among this young age group is important because younger children are also at highest risk of viral 14 and bacterial pneumonias 15 and subsequent hospitalizations 16 . Such a burden suggests the value of continued investment in Ecuador's pharmaceutical and nonpharmaceutical interventions to prevent respiratory illnesses, which were associated with an annual productivity loss of US$152 million 17 …”
Section: Discussionmentioning
confidence: 99%
“…As one of the most prevalent respiratory pathogens, the influenza virus causes millions of cases of severe illnesses worldwide annually, and it results in thousands of deaths, especially in young children and elderly patients ( 1 ). Laboratory, clinical, and epidemiological studies have shown that secondary bacterial infections significantly increase the morbidity and mortality of influenza virus infections, especially in high-risk individuals, such as the immunocompromised and immunosuppressed ( 2 , 3 ). It is reported that bacterial pneumonia is the predominant cause of death in pandemic influenza.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to remember that influenza represents a major cause of morbidity and mortality in older people [42]. Moreover, influenza is an important cause of other medical conditions in older subjects such as stroke and cardiovascular diseases [43], disability [44], pneumonia [45], and finally mortality. Vaccination against influenza in older people is highly effective in preventing all these conditions and therefore highly recommended [46].…”
Section: Discussionmentioning
confidence: 99%